The Effectiveness Of Using E-Money On The Smart Transportation Payment System In The City Of Jakarta - Syah Putra, Arman; Titin Herawaty, Mety; Aisyah, Nurul (International Journal of Educational Research & Social Sciences, 2022)
The background of this research is how to find out the effectiveness of the use of electronic money that is applied to the transportation system so that it can help the payment system to be more sophisticated and can help the wider community in making payments quickly in various sectors. The method used in this study is to use the literature review method and use quantitative methods, which use survey tools, with a survey, the data will be confirmed as real data, which can be useful in data processing so that you can find out the results of the data in field. The problem raised in this research is how to make payments quickly on a transportation system that is already advanced and sophisticated. With an electronic money payment system, it will be able to solve the problem of this research so that it can be seen that the payment system is more effective than the previous payment system. The purpose of this research is how to find out a variable is considered effective if it affects other variables, with a variable that is considered effective, the other variables will follow from the variables raised in this study, the variable raised in this study is electronic money, smart transportation payment system on the transportation system in Jakarta.